Modelling & Performing Analysis of an Alamouti Transmit Diversity System by using JTRAS Scheme & with Gold Code in different regions using MIMO System (International Journal of Engineering and Computer Science, 2017)
we consider a sub-optimum joint transmit receive antenna selection (JTRAS) scheme in multiple input multiple output(MIMO) systems equipped with N transmit and three receive antennas.At the transmitter,we keep one antenna as fixed and select the best among the remaining N-1 Antenna.After selecting two transmit antennas,we select the receive antenna for which the signal to noise ratio (SNR) is maximum.we assume spatially independent flat fading channels with perfect channel state information(CSI) at receiver and an ideal feedback link.we use Alamouti transmit diversity and derive the exact closed-form expression for the pdf of received SNR, using which we obtain bit error rate (BER) for BPSK constellation. We have presented simulation results and compared them with the derived analytical expressions. We have discussed some special cases of the considered antenna  performance of the considered scheme with the other available schemes in terms of number of feedback bits and BER. We conclude that the considered JTRAS scheme reduces number of feedback bits compare with the golden code.